Classification and Expression Profile of the U-Box E3 Ubiquitin Ligase Enzyme Gene Family in Maize (Zea mays L.) - Xiangnan Li; Longming Zhu; Zhenxing Wu; Jianjian Chen; Tingzhen Wang; Xiaoli Zhang; Gaofu Mei; Jian Wang; Guihua Lv (Plants, 2022)
The U-box E3 (PUB) family genes encode the E3 ubiquitin ligase enzyme, which determines substrate specific recognition during protein ubiquitination. They are widespread in plants and are critical for plant growth, development, and response to external stresses. However, there are few studies on the functional characteristic of PUB gene family in the important staple crop, maize (Zea mays L.). In this study, the PUB gene in maize was aimed to identify and classify through whole-genome screening. Phylogenetic tree, gene structure, conserved motif, chromosome location, gene duplication (GD), synteny, and cis-acting regulatory element of PUB member were analyzed. The expression profiles of ZmPUB gene family in maize during development and under abiotic stress and hormones treatment were analyzed by the RNA-seq data. A total of 79 PUB genes were identified in maize genome, and they were stratified into seven categories. There were 25 pairs of segmental duplications (SD) and 1 pair of tandem duplication (TD) identified in the maize PUB gene family. A close relationship was observed between the monocot plant maize and rice in PUB gene family. There were 94 kinds of cis-acting elements identified in the maize PUB gene family, which included 46 biotic- and abiotic-responsive elements, 19 hormone-responsive elements, 13 metabolic and growth-related elements. The expression profiles of maize PUB gene family showed characteristics of tissue specificity and response to abiotic stress and hormones treatment. These results provided an extensive overview of the maize PUB gene family.